Mevalonate kinase deficiency: an updated clinical overview and revision of the SHARE recommendations - Lengvári, Lilla; Takács, Kata; Lengyel, Anna; Pálinkás, Annamária; Wouters, Carine Helena; Koné-Paut, Isabelle; Kuemmerle-Deschner, Jasmin; Jeyaratnam, Jerold; Anton, Jordi; Lachmann, Helen Jane; Gattorno, Marco; Hofer, Michael; et al. (Frontiers in Immunology, 2024)
Mevalonate kinase deficiency (MKD), a rare auto-inflammatory disorder, arises from mutations in the MVK gene, disrupting isoprenoid biosynthesis, and affecting cellular processes. This comprehensive review provides an updated perspective on MKD, including its aetiology, pathogenesis, diagnostic modalities, and therapeutic strategies. Based on recent research and clinical advances, our objective is to bridge the knowledge gaps in the 2015 SHARE guidelines. By describing molecular mechanisms, diagnostic dilemmas, and emerging therapies, this article should serve as a resource for clinicians and researchers, promoting a deeper understanding of MKD and guiding optimal patient care.